Promazine Detection in Human Hair: Presentation of an LC-MS-MS Method and Pattern of Drug Discontinuation - Kintz, Pascal; Ameline, Alice; Raul, Jean-Sébastien (Journal of analytical toxicology, 2022)
Promazine is one of the oldest phenothiazine derivatives that have been proposed for the treatment of various psychiatric disorders. The drug is available as tablets, as syrups and in injectable forms. Despite its prescription to millions of subjects, its detection in human hair has seldom been reported. The aim of the present work is to develop a specific method to identify promazine in human hair by liquid chromatography-tandem mass spectrometry and to apply it to a patient who was self-medicating. The method involves overnight incubation of 20 mg of cut hair in 1 mL of pH 9.5 borate buffer in the presence of amitriptyline-d3 at 40°C. The chromatographic separation was performed using a reverse phase column HSS C18 with a gradient elution for 15 min. Linearity was verified from 0.5 to 500 pg/mg (r2 = 0.9996), after spiking blank hair with the corresponding amounts of promazine. The limit of detection was estimated at 0.1 pg/mg. The precision was lower than 20%. Promazine was detected in the hair of a psychotic subject at 228-270 pg/mg in a 3 × 1 cm segment. Given this was a patient who was self-medicating, her physician requested an immediate drug discontinuation. In a fresh hair specimen collected 3 months later, the proximal segment (0-1 cm) tested positive at 0.9 pg/mg, clearly indicating that the time to obtain a negative result after promazine discontinuation is about 3-4 months.Promazine is one of the oldest phenothiazine derivatives that have been proposed for the treatment of various psychiatric disorders. The drug is available as tablets, as syrups and in injectable forms. Despite its prescription to millions of subjects, its detection in human hair has seldom been reported. The aim of the present work is to develop a specific method to identify promazine in human hair by liquid chromatography-tandem mass spectrometry and to apply it to a patient who was self-medicating. The method involves overnight incubation of 20 mg of cut hair in 1 mL of pH 9.5 borate buffer in the presence of amitriptyline-d3 at 40°C. The chromatographic separation was performed using a reverse phase column HSS C18 with a gradient elution for 15 min. Linearity was verified from 0.5 to 500 pg/mg (r2 = 0.9996), after spiking blank hair with the corresponding amounts of promazine. The limit of detection was estimated at 0.1 pg/mg. The precision was lower than 20%. Promazine was detected in the hair of a psychotic subject at 228-270 pg/mg in a 3 × 1 cm segment. Given this was a patient who was self-medicating, her physician requested an immediate drug discontinuation. In a fresh hair specimen collected 3 months later, the proximal segment (0-1 cm) tested positive at 0.9 pg/mg, clearly indicating that the time to obtain a negative result after promazine discontinuation is about 3-4 months.